STUDENT SCIENTIFIC SOCIETY IN THE FIELD OF AVIATION AND COSMONAUTICS (1910-1920s) - Mikhail N. Okhotchinskiy (Высшее образование в России)
The article describes the activities of two student scientific associations that existed in 1920B1920s: the Circle for the study of Aeronautics and the Section of interplanetary connections, organized with an interval of twenty years in St. Petersburg (Leningrad) Institute of communications engineers. The author analyzes the main results of the activities of these organizations and shows the role of their supervisor Prof. Nikolay A. Rynin.